Pandangan Tokoh Agama Tamanan Terhadap Fenomena Pernikahan Usia Dini: (Studi Kasus Mansyarakat Tamanan) - Yusulli Yusulli; Fatimatus Sahro (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
Tamanan sub district is a developed sub district, always keeping up with the times. Especially with today's socialization, parents must also participate in monitoring the socialization of their children, because one of the factors causing underage marriage is uncontrolled socialization so they are afraid of causing accidents. The above fact is an interesting phenomenon to study. Therefore, it provides an opportunity for writing to analyze the factors that cause early marriage in Tamanan District. In addition, the opinions and solutions of religious leaders regarding early marriage.In this study, the research used by the compiler is a type of field research (field research), to the Tamanan KUA and several Tamanan religious leaders regarding their views on early marriage. The nature of the research used is descriptive, analytical, primary data, namely the original source without previous intermediaries, which is the source of data on the words or actions of a person who is observed or interviewed. In this study, the authors used Law No. 16 of 2019 concerning marriage, especially articles related to the discussion in this thesis. Based on the methods used above, it was revealed that the factors causing early marriage in the District itself, namely: environmental factors, economic factors and also factors regarding understanding of religion. these factors are what cause many early marriages in Tamanan District. Then the opinion of the figures is that there are some who agree with the existence of early marriage or in the legal language of marriage dispensation. Because there are dasrnya that allow marriage dispensation. Some religious leaders disagree with early marriage. Because a marriage needs readiness from various aspects. One of the figures agreed with early marriage, as long as the marriage was carried out in accordance with the terms and conditions.